2014
DOI: 10.1007/s00432-014-1771-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effects of artemisinin and resveratrol in cancer cells

Abstract: Taken together, the present study suggested that ART and Res possessed the synergistic anti-tumor effect. ART in combination with Res could be an effective therapeutic strategy for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Many studies show the synergistic effects of ARTs with other compounds or therapeutic approaches. The combined treatment of ART and resveratrol markedly inhibits cell proliferation and migration, and enhances apoptosis and ROS production in human cervical cancer HeLa and hepatocellular carcinoma HepG2 cells [213]. Similarly, the use of combined DHA and gemcitabine exhibits strong synergistic effects on the loss of mitochondrial membrane potential and induction of apoptosis in human NSCLC A549 cells [214].…”
Section: Artemisininsmentioning
confidence: 99%
“…Many studies show the synergistic effects of ARTs with other compounds or therapeutic approaches. The combined treatment of ART and resveratrol markedly inhibits cell proliferation and migration, and enhances apoptosis and ROS production in human cervical cancer HeLa and hepatocellular carcinoma HepG2 cells [213]. Similarly, the use of combined DHA and gemcitabine exhibits strong synergistic effects on the loss of mitochondrial membrane potential and induction of apoptosis in human NSCLC A549 cells [214].…”
Section: Artemisininsmentioning
confidence: 99%
“…The finding was in agreement with previous studies, where it has been reported that deguelin, a flavonoid compound increase antitumor activity of cisplatin against gastric cancer cells. 16 Furthermore, another study also reported that triptolide, a diterpene from Tripterygium wilfordii in combination with cisplatin produced a synergistic anticancer effect in gastric cancer cells. By this combination, triptolide increased apoptosis effect of cisplatin through activation of caspase-3 and caspase-9.…”
Section: Resultsmentioning
confidence: 99%
“…Synergistic study − The interaction of flavonoid compounds with cisplatin was determined using an isobologram analysis as previously described with slight modification. 16 Briefly, the dose-dependent effects of each compounds and fixed concentrations of compound were determined using MTT assay. The cells were then treated with a combination of flavonoid compounds and cisplatin.…”
Section: Percentage Inhibition (%) =mentioning
confidence: 99%
“…The proportion of apoptosis (sub-G1 cell cycle accumulation) and DNA fragmentation were increased more significantly by the combination compared to single-agent treatments [37]. Resveratrol elicited more significant inhibitory effects on ovarian and hepatocellular carcinoma cells when combined with artemisinin at a ratio of 2:1 by increasing apoptosis, ROS levels and by decreasing migratory ability [38]. Combinations of resveratrol with matrine, genistein and arsenic trioxide have been used in the treatment of hepatoma, breast cancer and acute and chronic myeloid leukemias [39-41].…”
Section: Synergistic Effects Of Chm Compounds Chms Combinations and mentioning
confidence: 99%